Teduh / Annisaa ‘Izzati Abdul Rauf and Afzanizam Muhammad - Abdul Rauf, Annisaa ‘Izzati; Muhammad, Afzanizam (2024)
The design of public spaces is an important factor in guaranteeing people's comfort and welfare, especially in university settings. These areas are central to the definition of tone and functionality at places like campuses. Eco-friendly elements, comfortable furniture arrangements and intriguing visual effects make such places comfortable for various kinds of activities. Also, large, open spaces provide natural features such as light and air, which makes the whole concept a positive one. Such spaces are communal and can be used to facilitate learning in an environment that is safe and encouraging to the user. They can be adapted according to the activities to be performed; thus, different groups and their interests as well as needs can be met.